Journal of Human Sport and Exercise - 2018 - Spring Conferences of Sports Science 2018
DOI: 10.14198/jhse.2018.13.proc2.17
|View full text |Cite
|
Sign up to set email alerts
|

High level performance in world judo circuit: Notational analyzes of combat phase by weight categories

Abstract: This study analysed the time dedicated in the different phases of combat in all male weight divisions. For this, we analysed 548 combats. This time-motion analysis was performed through a previously-validated protocol. The main results indicated a significant effect for approach (p≤0.001), where the Half-Middleweight division showed a higher frequency vs. the others, except Half-heavyweight. For attack, Half-Lightweight showed a higher frequency versus Heavyweight (5.7±4.8 vs. 4.6±3.5 attempts; p=0.004). Extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…The 8 studies that met the eligibility criteria in this systematic review were: Adam et al (2013) , Segedi et al (2014) , Boguszewski (2016) , Sterkowicz-Przybycien et al (2017) , Díaz-de-Durana et al (2018) , Barreto et al (2019) , Soriano et al (2019) , and Ceylan and Balci (2020) . Table 1 shows the qualitative analysis of these articles.…”
Section: Resultsmentioning
confidence: 99%
“…The 8 studies that met the eligibility criteria in this systematic review were: Adam et al (2013) , Segedi et al (2014) , Boguszewski (2016) , Sterkowicz-Przybycien et al (2017) , Díaz-de-Durana et al (2018) , Barreto et al (2019) , Soriano et al (2019) , and Ceylan and Balci (2020) . Table 1 shows the qualitative analysis of these articles.…”
Section: Resultsmentioning
confidence: 99%
“…Investigations conducted weight division comparisons to provide further insights in the relationship between key-morphological variables and performance analysis 5 . When expensive high technology (ex.…”
Section: Importance Of Technical-tactical Analysis For Modern Traininmentioning
confidence: 99%
“…Regarding the gripping phase, there is a range of primary and secondary factors influencing the development of judo expertise which need more research: gripping associated with high levels of power and produced torque appear to be one of the essential characteristics that determine success in competition 7 . Past study showed that middleweight athletes had higher gripping frequencies than other weight categories, particularly gripping more often with one hand targeting their opponent's back and sleeves 5 . Recent findings outline the relationship between balance control and the bilateral reactionary gripping task.…”
Section: Importance Of Technical-tactical Analysis For Modern Traininmentioning
confidence: 99%
See 1 more Smart Citation
“…Technical-tactical behavior analysis have been well-described in judo, verifying match demands (Coswig et al, 2018), techniques and muscle group specific torque production (Lech et al, 2015). Specifically, during female and male judo adult's competition, technical-tactical actions of different technical-tactical behaviors and pause strategies are highly varied and the associations between these variables together describe a judo's system of attack or fighting style (López Díaz- de-Durana et al, 2018). Despite this important finding about the senior age class, until now, it is not very clear whether there are technical-tactical behavior differences between female and male youngers.…”
Section: Introductionmentioning
confidence: 99%